Safety assessment of high voltage substation earthing systems with synthetic geotextile membrane - Mostafa Nazih (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2019)
High voltage substations built within areas prone to vegetation or with unfavourable subgrade conditions are paved with the addition of punched geotextiles and non-conductive synthetic fabrics underneath switchyard surfacing. The aim of this research is to identify the impact of synthetic textiles on earthing system performance through numerical analysis with the state-of-the-art software package. The new layer interferes with the earthing grids performance with a different behaviour depending on the installation above or underneath the layer with considerable impact taking place when the earthing grid is installed above the geotextile layer. Rods penetrating the geotextile can alleviate the potential voltage distribution issues and improve the earthing system performance regardless of the native soil stratification.